2015
DOI: 10.1002/jsfa.7275
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polycyclic aromatic hydrocarbons in smoked buffalo mozzarella cheese produced in Campania Region, Italy

Abstract: It was found that the consumption of this typical food of Campania does not represent a risk for consumers, considering that the incidences on EFSA dietary intake were always lower than 1.5% for mozzarella cheese and lower than 3% for smoked mozzarella cheese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…They also indicated that small cheeses (i.e., those with a smaller cheese-to-rind ratio) displayed the highest levels of PAHs. Fasano et al [77] observed similar findings when evaluating traditionally smoked cheese samples obtained in Spain. According to the findings of these studies, almost all PAHs were present in the cheese rind.…”
Section: Milk Dairy and Baby Foodsmentioning
confidence: 54%
See 1 more Smart Citation
“…They also indicated that small cheeses (i.e., those with a smaller cheese-to-rind ratio) displayed the highest levels of PAHs. Fasano et al [77] observed similar findings when evaluating traditionally smoked cheese samples obtained in Spain. According to the findings of these studies, almost all PAHs were present in the cheese rind.…”
Section: Milk Dairy and Baby Foodsmentioning
confidence: 54%
“…Several studies investigated the presence of PAHs in milk, dairy, and baby [74,77,80,[112][113][114][115]. Fresh milk contamination is associated with environmental pollution, especially that produced by biomass burning.…”
Section: Milk Dairy and Baby Foodsmentioning
confidence: 99%
“…PAHs can be found in food products as a consequence of certain industrial processing methods such as smoking, grilling, roasting and drying; these are important sources of PAH contamination of seeds, edible oils, meat and dairy products . Alomirah et al speculated that diet contributes 88–98% to PAH exposure, especially in the case of non‐smoking and non‐occupationally exposed populations . Therefore, PAHs in processed foods have attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…La presencia de estos compuestos en el aire en forma de material particulado fue informada a nivel global (4) , y también sus depósitos y acumulación en suelos y pastos (5,6) . Cuando los pastos son consumidos por vacas en estado de lactación, se ha demostrado su presencia en leche y derivados lácteos (7)(8)(9)(10)(11) . La contaminación de leche con HAP, depende de factores ambientales, como son: la fuente de exposición, la etapa de lactancia, el estado de salud del animal y del sistema de crianza (12,13) .…”
Section: Introductionunclassified
“…No existe un método oficial para la determinación de HAP en leche, existiendo dos tendencias en la identificación y cuantificación de los mismos: 1) por cromatografía gaseosa empleando detector de ionización de flama y espectrometría de masas (15,16) , 2) por cromatografía de líquidos de alta resolución con detector de fluorescencia (7,8,17) . Para obtener mejores resultados en la preparación de las muestras se han empleado diferentes procedimientos que incluyen saponificación, extracción líquido-líquido (LLE) y limpieza por cromatografía en columna o más recientemente, extracción en fase sólida (SPE) (18,19,20) .…”
Section: Introductionunclassified